Clinical, dermoscopic, and histopathological correlation of lichenoid dermatoses - Praveen Kumar Shanmugam Reddy; Tharayil Kunneth Sumathy; Arakali Lakshminarayana Shyamprasad; Kanakapura Nanjundaswamy Shivaswamy; Madivalara Yallappa Suparna (Wolters Kluwer Medknow Publications, 2019)
Context: Lichenoid disorders are diverse, and the use of a noninvasive tool like dermoscopy could highlight the pathology in the deeper skin. The present study aimed to compare the accuracy of clinical and dermoscopic findings with histopathology in making a diagnosis of lichenoid dermatoses. Settings and Design: This is a prospective cross-sectional observational study of consecutive, clinically suspected cases of lichenoid skin eruption. Subjects and Methods: Forty patients with various clinical features and dermoscopic features were enrolled. Skin biopsy was taken from all the cases, and the clinical, dermoscopic, and the histopathological correlation was made. Results: Classical lichen planus (CLP) was the most common entity reported (30%), followed by hypertrophic LP (HLP) (15%) and lichen nitidus (15%). Radiating lines were the most common structures seen in as compared with HLP. Comedo-like lesions were significantly seen in HLP than CLP. Compact hyperkeratosis was seen in 66.67% of CLP and in all cases of HLP. There was a significant association in HLP, between blue and black structures on dermoscopy as compared with pigmented melanophages in dermoscopy. Chi-square test was used as a method of comparison, and SPSS Inc. Released 2009. PASW Statistics for Windows, Version 18.0. Chicago: SPSS Inc. was used. Conclusion: Dermoscopic findings give a vital clue about the underlying histopathology which can aid a physician in his/her diagnosis.